Evaluating the Legal Basis of a Rule-Based Organisation of ASEAN - Arundhati, Gautama Budi; Koesrianti, Koesrianti; Hastuti, Lina (Universitas Airlangga, 2025)
This article examines whether the structure of the 2008 ASEAN Charter is still well-suited and appropriate with the intergovernmental organisation of ASEAN. ASEAN has developed and turned into a rule-based organisation. The Charter as the legal basis of the Association is regarded as the constitution of ASEAN, and it has the constitutional character as if all ten ASEAN Member States (AMS) were united as one big country. The design and character of the Charter have placed it above the AMS’s constitutions. While ASEAN basically stands firmly to state’ sovereignty and non-interference principles which were and will remain the important ASEAN principles, ASEAN has developed into a people-oriented organisation which accommodates the participations of the ASEAN people into the Association. By analysing the normative ASEAN and international legal instruments that are gathered from the official ASEAN website and other publicly available sources, combined with the conceptual and statute approaches, this article found that ASEAN has become a legalised organisation. ASEAN surely cannot be equated with the European Union (EU), considering that the TFEU provides a hierarchical arrangement and the binding effect upon its member countries. The article argues that the Charter has a supremacy at regional level as a part of the indirect aspects of the community law of ASEAN.